Spatial Optimisation Of Oil Palm Biomass Co-Firing For Emissions Reduction In Coal-Fired Power Plant - Hashim, Haslenda; Razak, Nurul Hanim; Mohd Idris, Muhammad Nurariffudin (Elsevier Ltd., 2018)
Due to the rising concerns on climate issues, the transitions of fossil fuels to renewable energy are highly promoted globally. Malaysia which has abundant sources of biomass, is maximising the efforts to increase renewable energy shares in the current energy mix. Biomass co-firing with coal offers a promising route to less greenhouse gas (GHG) emissions due to the zero net greenhouse effect of biomass combustion. This paper presents an integrated spatial optimisation model of biomass co-firing supply chain for existing power generation facilities through the integration of geographical information system (GIS) and mixed-integer linear programming (MILP). The model integrates spatial distributions of biomass supply, locations to build biomass pre-treatment facilities, location-allocation of supply and demand of biomass co-firing supply chain and economic and environmental sounds of biomass co-firing system. The optimisation of the whole supply chain system is conducted with the aim to minimise the overall cost and its emissions while determining the most optimal locations to build pre-treatment facilities to support co-firing power generation. Based on the findings, the cost factors of deploying co-firing technology in existing coal-fired power plant are between 56.61 and 61.65 USD/MWh for 10e50% co-firing rates as compared to the base case electricity generation cost which is at 56.29 USD/MWh. Minimum differences in cost factors are achieved when dedicated fossil fuels scenario is compared to several cofiring scenarios. Up to 8.83 x 106 t of CO2 (equivalent to 46% of CO2 reduction) can be reduced annually in Johor as a result of this practice. This shows that co-firing technology is promising to be implemented in Malaysia while achieving significant emissions reduction target with incentives supported by government.